Short Communication: Polymorphism of myostatin gene and its association with body weight traits in a hybrid of GAMA chicken (Gallus gallus domesticus Linn. 1758) - ARDO TANJUNG; H.T.S.S.G. SARAGIH; TRIJOKO; H.P. SOENARWAN; S. WIDIANTO; I.W.S. MAHARDHIKA; B.S. DARYONO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Tanjung A, Saragih HTSSG, Trijoko, Soenarwan HP, Widianto S, Mahardhika IWS, Daryono BS. 2019. Polymorphism of myostatin gene and its association with body weight traits in a hybrid of GAMA chicken (Gallus gallus domesticus Linn. 1758). Biodiversitas 20: 3207-3212. An experiment was conducted to detect SNP of the myostatin gene and its association with the body weight of hybrid chicken crossbreed from F1 Kamper and BC1 Broiler. Four F1 Kamper hens were crossbred with BC1 Broiler rooster. Day old chick (DOC) hatched were maintained for 49 days with body weight measurement every seven days. The blood samples from 49 days old chicken were taken for DNA isolation by Chelex 5% method and then amplification of the myostatin gene. PCR products were sequenced, and sequence alignment was performed using Clustal Omega to obtain SNP. The SNP obtained was analyzed by the Pearson correlation test with the body weight of forty nine-days-old chickens. The body weight of the hybrid chicken is higher than of Pelung chicken but lower than the Broiler. There are 7 SNPs in myostatin gene exons included 2 Adenine insertions, 1 Guanine deletion, and four substitutions (C2244G, G2283A, T4842G, G7378T) that yield nine haplotypes. Six haplotypes had different protein sequences with Myostatin protein, while three haplotypes were identical to Myostatin protein. The correlation analysis showed that there was a strong positive correlation (r = 0.736) between normal Myostatin protein and mutant to chicken body weight at 49-days-old. Adenine insertion to nucleotide 2099-2100 of myostatin gene had a very strong positive correlation (r = 0.800) to 49-days-old chicken body weight, although T4842G substitution had a strong negative relationship (r = -0.773) to 49-days-old chicken body weight. Adenine insertion to nucleotide 2099-2100 of myostatin gene could be a genetic marker of heavier body weight of the hybrid chicken.